THE EFFECT OF COFFEE ON THE SPERMATOZOA MOTILITY OF MALE WISTAR RATS (Rattus norvegicus) EXPOSED TO ELECTRIC CIGARETTE SMOKE - Erika Shinta Avianty; Puspita Kusuma Dewi; Amallia Nuggetsiana Setyawati; Arufiadi Anityo Mochtar (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2021)
Background: Man infertility was caused by decrease of spermatozoa quality. E-cigarette smoke which contained chemicals as nicotine could produce free radicals which decreased spermatozoa motility. Coffee was contained of caffeine and chlorogenic acid functioned as antioxidant and increase spermatozoa motility. Aim: To prove the coffee giving effect to spermatozoa motility of male wistar rats that have been exposed to e-cigarette smoke. Methods: The sample were 28 male wistar rats (Rattus norvegicus), no anatomical abnormalities, 200-300 grams, and 8-9 weeks. The sample was randomly divided into 4 groups: no treatment, the rats which were exposed to e-cigarette smoke, the rats which were given 3ml robusta coffee solution contained of 180mg coffee powder and exposed to e-cigarette smoke, the rats which were given 3ml robusta coffee solution contained of 360mg coffee powder and exposed to e-cigarette smoke. The coffees solution was given through a gastric swab. The e-cigarette liquid doze was 3,5ml with 18mg/ml nicotine for each group. After four weeks, the rat’s sperm sample was taken, preparation was made, and spermatozoa motility was examined through microscope. The statistical test exerted Saphiro-Wilks test and non-parametrical test from Kruskal-Wallis. Results: The mean of spermatozoa motility percentage in progressive, non-progressive, and negative control group immotility = (53,81±6,507), (30,00±5,444), (16,66±3,333); positive control = (0,48±1,259), (17,14±18,604), (82,38±19,787); first treatment = (10,00±4,304), (32,85±14,065), (57,14±17,259); second treatment = (11,42±1,779), (26,19±8,033), (62,38±8,760). Kruskal-Wallis test showed a significant difference in progressive motility and immotility (p=0,000). Conclusion: The coffee solution could give an effect on the spermatozoa motility of male wistar rats exposed to electric cigarette smoke. Keywords: Infertility, e-cigarette, nicotine, coffee, motility